Understanding architectural education in Australasia. - Ostwald M. J.; Williams A. (Australian Learning and Teaching Council, 2008)
Volume 1 describes the background to the architecture discipline in Australasia and it outlines the methods used to inform the present research. The content of this volume is centred on (1) architecture schools, programs and curricula, (2) architectural academics and students and (3) teaching and learning in architecture schools. Volume 2 summarises the results of the research and provides a series of recommendations for the architecture discipline and the professional bodies that represent architects in Australasia. Volume 2 also includes a brief summary of the research method, its scope and limitations, and an overview of the issues facing the architecture discipline in Oceania.[p.6, ed]